Assessing the Link Between Learning Results in Physical Education and Basic Motor Skills with Students’ Sports Preferences - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, Muh. Sahib (Universitas Majalengka, 2025)
This study aimed to assess the relationship between physical education (PE) learning outcomes, basic motor skills, and students’ sports preferences at SMP Negeri 33 Makassar. A correlational quantitative research design with a descriptive-analytic approach was employed. The sample consisted of 120 students from grades VII and VIII, selected through stratified random sampling. Data collection involved PE learning scores, motor skill tests (20-meter sprint, standing long jump, ball throw, one-leg balance), and a structured questionnaire measuring sports preferences. Descriptive statistics showed that the average PE score was 78.5 (SD = 7.2), while motor skill test scores varied: sprint (mean = 4.9 seconds, SD = 0.5), long jump (mean = 1.7 meters, SD = 0.3), ball throw (mean = 8.2 meters, SD = 1.1), and balance (mean = 12.4 seconds, SD = 3.2). Pearson correlation analysis revealed significant positive relationships between PE learning outcomes and sports preferences (r = 0.54, p < 0.01), and between motor skills and sports preferences (r = 0.62, p < 0.01). Multiple regression indicated that PE learning outcomes and motor skills together explained 37.1% of the variance in sports preferences (R² = 0.371, p < 0.001), with motor skills having a stronger predictive influence (β = 0.48). These findings emphasize the importance of integrating cognitive and motor skill development in PE programs to enhance students’ interest in sports. This study contributes to improving physical education strategies to promote active lifestyles among adolescents.